Education - Basic pillar of the sustainable rural development. Evolutions and gaps in the South-Muntenia region - Sorinel Ionel Bucur (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The sustainable development of an economy, either viewed as a whole or at the local level, is based on at least two essential pillars, namely the stock of human resources and the educational system. If the demographic system is the backbone of development, education plays an important role at least in terms of building a system of values related to structural changes in the economy. Although at the level of rural communities there is often opposition to further studies, generated either by the local behaviours, specific to each area, or by the lack of motivations in this field, investments in this field should be in the first place. In this context, the present approach aims to carry out an analysis of the educational system in the rural area of the South-Muntenia region, as an essential element of the local sustainable development process.
Keywords: Q01; Q19; R11; R19; 330; educational system; gaps; regional dimension